The Promoting Effect of Sports Culture on Cultivating College Students’ Psychological Quality of Innovation and Entrepreneurship - Wenyan Fu (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
In order to understand the promoting effect of college students' innovation and entrepreneurship psychological qualities, the author proposes a study based on the promoting effect of sports culture on cultivating college students' innovation and entrepreneurship psychological qualities. A questionnaire survey was conducted to randomly distribute student questionnaires according to different colleges, majors, and grades, a total of 800 student questionnaires were distributed, and 737 questionnaires were collected, with a recovery rate of 92%, 663 valid questionnaires were collected, and the effective rate was 90%; 32 questionnaires were distributed to physical education teachers, and 31 questionnaires were collected, with a recovery rate of 97%, there were 29 valid questionnaires, with an effective rate of 94%. Campus sports culture plays a positive role in improving the psychological quality of college students, promoting their spiritual civilization, and cultivating their lifelong sports awareness. Through questionnaire survey and analysis, this study investigates the promoting effect of campus sports culture on the psychological quality of innovation and entrepreneurship among college students. It proposes implementation paths such as enhancing the cultivation of value identity, creating a range of sports culture, optimizing the sports curriculum system, and leveraging the leading role of teachers, in order to provide reference for relevant research in this field.